Issues of Bai’ al-‘Inah in the contemporary Islamic financial products and its solutions according to the shariah principles - Sawari, Mohd Fuad; Nik Abdullah, Nik Azizu; Mat Jubri@Shamsuddin, Mustafa; Abdul Aziz, Akhtarzaitie (Zes Rokman Resources, 2018)
Bai’ al-‘inah is one of the well-known sale-based contracts among Islamic financial products. This type of contract has been applied by most of the Islamic Financial Institutions (IFI) particularly in Malaysia towards their Islamic financial products.Although all the controversial issues related to bai’ al-‘inah have already been discussed before by Fiqh scholars, due to the implementation of the underlying Shariah concept of Bai’ Al-‘Inah in current Islamic financial products, it appears that new issues relating to ‘inah have appeared and need to be deliberated further by contemporary Islamic scholars to ensure that it is in line with the development of Islamic financial products. One of the main Shariah issues that has occurred in bai’ al-‘inah based contracts is the sequence of the implementation of the aqad (contract) between the bank and the customers. Hence, this research will focus on this issue from several points of view, which include the causes that lead to the issue, the best solutions according to the Shariah to rectify the issue, and the consequences of the affected accounts if the issue is a Shariah compliance issue. Besides that, this research also will try to explore the solutions and decisions from the Shariah Committees of some of the Islamic banks in Malaysia. Thus, this research will try to briefly state the decisions of the three banks that operate Islamic bank licenses, which are AmIslamic Bank, Bank Simpanan Nasional and Agro Bank. In order to focus on the main issue of this research, which is the sequence of aqad, the researcher will also try to explore that issue in some of the Islamic products that apply bai’ al-‘inah as the underlying Shariah contracts, mainly on personal financing and home financing.